Title DEVELOPMENT AND VALIDATION OF SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF LEUKOTRIENE RECEPTOR ANTAGONIST MONTELUKAST SODIUM IN BULK AND PHARMACEUTICAL FORMULATIONS - EL SHEIKH, RAGAA; S HASSAN, WAFAA; M EL-GABRY, MARWA; GOUDA, AYMAN A; S IDRIS, SALEH; M SALEM, OSAMA; S ALI, IBRAHIM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Simple, sensitive, precise, reproducible, and validated visible spectrophotometric methods have been developed for the determination of leukotriene receptor antagonist drug, namely, montelukast (MNT) sodium in bulk and pharmaceutical preparations. Methods: Three spectrophotometric methods are based on the formation of yellow-colored ion-pair complexes between MNT sodium and three dyes, bromocresol green, bromophenol blue, and methyl orange with absorption maxima at 420, 416, and 426 nm, respectively. Results: The stoichiometric ratio of the formed ion-pair complexes was found to be 1:1 (drug:reagent) for all methods, as deduced by Job’s method of continuous variation. Several parameters such as pH, buffer type and volume, reagent volume, sequence of addition, and effect of extracting solvent were optimized to achieve high sensitivity, stability, low blank reading, and reproducible results. Under the optimum conditions, linear relationships with good correlation coefficients (0.9993–0.9999) were found over the concentration ranges of 1.0–10, 1.0–12, and 1.0–16 μg/mL with a limit of detection of 0.30, 0.29, and 0.27 μg/mL for bromocresol green, bromophenol blue, and methyl orange methods, respectively. Conclusion: The proposed methods were validated in accordance with ICH guidelines and successfully applied to the analysis of MNT sodium in pharmaceutical formulations. Statistical comparison of the results obtained by applying the proposed methods with those of the reference method revealed good agreement and proved that there was no significant difference in the accuracy and precision between the results.